Effect of dressing with different antiseptic agents on reproductive parameters in rats undergoing abdominal incision - Akarsu, G. D.; Erbas, E.; Akarsu, S. A. (Polska Akad Nauk, Polish Acad Sciences, Univ Warmia & Mazury Olsztyn, 2024)
Antiseptic agents used in the postoperative period affect the functions of many tissues in the body, including the testicles. In this study, the effect of dressings administered with different antiseptic agents on testicular functions in rats that underwent abdominal incisions was investigated. A total of 48 Sprague-Dawley rats were used in the study. Each of the rats in the study group underwent a 4 cm -long skin and muscle operation. The incision was then stitched immediately. Antiseptics, hemp seed oil, hemp leaf oil, and cannabidiol oil were then administered to the rats for 10 days to provide antisepsis. The rats were sacrificed 24 hours after the last administration, and testicular tissues were removed. Testicular tissues were used for histopathological examination and biochemical analysis, while epididymal tissue was used for sperm analysis. According to the results, the MDA level in the antiseptic -administered group was higher than in the other experimental groups (p<0.05). Levels of SOD, CAT activities, and GSH content were found to be lower in the antiseptic group than in the hemp seed oil, hemp leaf oil, and cannabidiol oil groups (p<0.05). In testicular histology, the SEED group had the highest Johnsen score, and the antiseptic group had the lowest score (p<0.05). While JAK, P-JAK2, STAT3, PSTAT3, and NF-kappa B were generally higher in the antiseptic group compared to the other groups, they were lower in the SEED group. Additionally, sperm total motility rate and epididymal sperm density were highest in the SEED group (p<0.05). As a result, it was determined that cannabidiol seed oil had a good effect on testicular histology and sperm quality in male rats during the wound healing
Keywords: antiseptic; hemp; oxidative stress; testis; wound healing